THE EFFECT OF ONLINE CUSTOMER REVIEWS ON BOOKING INTENTION: THE MEDIATING ROLE OF TRUST AND PERCEIVED VALUE IN THE HOTEL INDUSTRY - Harbiyah Gani; Ichsan Akmal Mazas; Aida Fitri (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2026)
The rapid growth of digital platforms has transformed consumer decision-making processes in the hospitality industry, particularly through the increasing reliance on online customer reviews. This study aims to examine the effect of online customer reviews on booking intention, with trust and perceived value serving as mediating variables. Drawing upon signaling theory and consumer behavior theory, this research proposes that online reviews function as informational cues that shape consumers’ cognitive and affective evaluations before making reservation decisions. A quantitative approach was employed using survey data collected from hotel customers who actively use online travel platforms such as Traveloka, Booking.com, and Tripadvisor. The data were analyzed using SPSS to test both direct and indirect relationships among variables. The findings indicate that online customer reviews significantly influence booking intention, both directly and indirectly through trust and perceived value. Trust and perceived value are found to partially mediate the relationship, suggesting that consumers are more likely to make hotel reservations when reviews enhance their confidence and perceived benefits. This study contributes to the hospitality marketing literature by providing empirical evidence on the psychological mechanisms underlying digital review influence and offers managerial implications for hotel marketers in optimizing online reputation strategies.